Answer:
h(d)= -2d^2 +4d +6
Step-by-step explanation:
Vertex (1,8)
Landing Point (3,0)
Applying the vertex formula, a quadratic equation can be described by its vertex v(x,y) as follows:
[tex]h=a*(d-x)^2 +y[/tex]
Since the vertex in this situation is at v (1,8):
[tex]h=a*(d-1)^2 +8[/tex]
To solve for 'a', apply the other given point (landing point) into the equation:
[tex]0=a*(3-1)^2 +8\\4a= - 8 \\a=-2[/tex]
Expanding the equation yields:
[tex]h=-2*(d-1)^2 +8\\h=-2(d^2 -2d +1) +8\\h= -2d^2 +4d +6\\[/tex]